Design and development of smart cover system for vineyards - Bilal Karaman; Sezai Taskin; Daudi S. Simbeye; Mbazingwa E. Mkiramweni; Aykut Kurtoglu (Smart Agricultural Technology, 2023)
With the abrupt change of climatic conditions every year, the effect on nature increases visibly. Grape producers experience the effects of climate change negatively. For example, frost, hail, and extreme temperatures are undesirable conditions for grape producers. When any of these natural events occur, they can greatly damage grape crops. In this study, a cover system that can be opened and closed automatically has been developed against undesirable natural events that vineyards are exposed to. The developed system consists of a DC gear motor capable to open and close the vineyard cover, a control card that collects the information from the sensors (rain sensor, temperature sensor, hail sensor, and frost sensor) and interprets the results, a solar battery that will store energy, a PV panel that will charge the battery, and mechanical components. In this work, an easily portable prototype was studied. The dimensions of the design have been realized as 1/3 of the dimensions of the real system. The system is designed to be 1 m high and 2 m wide. The control card of the system is designed to be suitable for outdoor conditions. Moreover, a remote management and condition monitoring of the system have been realized via a mobile application. Thus, it was aimed to increase the productivity of the vineyards and to protect the grapes.